Spatial housing economics: A survey - Meen, Geoffrey (Urban studies (Edinburgh, Scotland), 2016)
This introduction to the virtual special issue surveys the development of spatial housing economics from its roots in neoclassical theory, through more recent developments in social interactions modelling, and touching on the role of institutions, path dependence and economic history. The survey also points to some of the more promising future directions for the subject that are beginning to appear in the literature. The survey covers elements of hedonic models, spatial econometrics, neighbourhood models, housing market areas, housing supply, models of segregation, migration, housing tenure, subnational house price modelling including the so-called ripple effect, and agent-based models. Possible future directions are set in the context of a selection of recent papers that have appeared in Urban Studies. Nevertheless, there are still important gaps in the literature that merit further attention, arising at least partly from emerging policy problems. These include more research on housing and biodiversity, the relationship between housing and civil unrest, the effects of changing age distributions – notably housing for the elderly – and the impact of different international institutional structures. Methodologically, developments in Big Data provide an exciting framework for future work.